2017
DOI: 10.9734/ijtdh/2017/34381
|View full text |Cite
|
Sign up to set email alerts
|

A Report on Applying Digital Epiluminescence Dermoscopy to Guide Topical Treatment for Generalised Vitiligo

Abstract: We have reported on utilising digital epiluminescence dermoscopy to detect the sparing of perifollicular pigments in localised vitiligo. These spotty zones might be the most acute autoimmune battle line. We saw a 68-year-old gentleman with five-year history of segmental/generalised vitiligo. He declined systemic treatments. These spotty zones mentioned above were identified by epiluminescence dermoscopy. We advised him to apply a very potent topical corticosteroid two times per week to these zones. Much improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…We discovered and reported for the first time the visualisation of such pattern at the dermoscopic magnification level [23]. We then further reported that identification of such zones by ED could enhance the localisation of regions with high autoimmune activity, and hastened efficacy of drug treatments [24].…”
Section: Researchmentioning
confidence: 90%
“…We discovered and reported for the first time the visualisation of such pattern at the dermoscopic magnification level [23]. We then further reported that identification of such zones by ED could enhance the localisation of regions with high autoimmune activity, and hastened efficacy of drug treatments [24].…”
Section: Researchmentioning
confidence: 90%